Organoleptic Test of Jelly Candy Made from Starfruit - Saputra, I Kadek Agus Artha; Martadjaya, I Gusti Made Iwan Dusanta; Sudiarta, Ngakan Putu (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
This study examines the development of starfruit-based jelly candy as an innovation of local food products. Organoleptic tests were conducted to assess the quality of taste, aroma, texture, and color involving 30 panelists. The results showed that starfruit jelly candy has very good organoleptic quality with high scores on all tested variables. This jelly candy is considered to have great potential to be developed as a healthy food product with high economic value. This study opens up opportunities for diversification of starfruit-based products and suggests further research related to nutritional analysis, product stability, and commercialization strategies.